PERAN PSIKOLOGI DALAM PENDIDIKAN ISLAM - Hanik Rahmawati Solikhah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Psychology plays an essential role in Islamic education, especially in understanding students' character, emotions, and developmental stages. Islamic education focuses not only on knowledge acquisition but also on moral and spiritual development. This article aims to describe the relationship between psychology and Islamic education and its application in learning processes. The method used is literature study with a descriptive-qualitative approach. The findings indicate that the integration of psychological and Islamic values enhances learning strategies, character development, and students’ mental well-being. Islamic psychology, which emphasizes the balance of the physical and spiritual aspects, becomes a key approach in value-based education.